ASUHAN KEPERAWATAN PADA TN.G DENGAN TUBERCULOSIS PARU TERHADAP PENURUNAN SESAK NAFAS DENGAN PEMBERIAN POSISI SEMI FOWLER DI RUANG RAWAT MAWAR RUMAH SAKITHARAPAN BUNDA - Hariyati Elias Lobang; Ns. Trisya Yona Febrina, Ns. Afif D Alba (CV. ADIBA AISHA AMIRA, 2024)
The phenomenon of public health problems, especially pulmonary TB in the era of globalization, is not underestimated. Pulmonary Tuberculosis is a chronic bacterial infection disease that is persistent and chronic so that clinical symptoms will only appear if it is severe and requires treatment for a long time. The purpose of this professional scientific paper is to analyze the semi-Fowler's position intervention to reduce shortness of breath in pulmonary TB patients at Harapan Bunda Hospital. The method in this final scientific paper is a case study with a quasi-experimental method. From the results of case analysis in patients, it was found that there was an effect of semi-Fowler's position on decreasing shortness of breath in pulmonary TB patients. The conclusion of this nursing care is that the semi-Fowler's position is very effective because it can reduce the shortness of breath experienced by the client and can make the client feel comfortable. So giving a semi-Fowler's position in pulmonary TB patients can overcome shortness of breath because by using gravity to help expand the lungs and reduce pressure from the abdominal visceral to the diaphragm it can be lifted and the lungs can develop optimally.